New records of the association between Polybia rejecta (Fabricius, 1798) (Hymenoptera: Vespidae) and Azteca chartifex Emery, 1896 (Hymenoptera: Formicidae) for the Caatinga and Amazon forest - Somavilla, Alexandre (2020)
Some neotropical social wasps are associated with certain vertebrates and other insects, like ants. These interactions have been reported for decades, but little is known about these associations in the caatinga biome. This study describes the first association record between the nests of Polybia rejecta wasps and Azteca chartifex ants in the caatinga of Piauí state and presents new records for Amazonas. This study supports the hypothesis that the association between the social wasps P. rejecta and A. chartifex ants is more common than previously documented. This new finding reinforces this association between different species not only for the Amazon and atlantic forest, but also for the caatinga biome.